EXAMINING THE ROLE OF TEACHERS IN REFORM OF EARLY CHILDHOOD EDUCATION IN INDONESIA - Waode Eti Hardiyanti; Muhammad Ilham; Aris Suziman (Jurnal Sultra Elementary School, 2020)
Abstract: The Early Childhood Education (ECE) in Indonesia has experienced major change due to government policy in the last ten years. The aim of this paper is to explore and examine the implications of the policy for the Early Childhood teachers using Foucault’s concepts as important guides for this discussion. There are three major changes that indicate the reform of ECE, (1) the need of improving the early childhood teachers’ qualification; (2) monitoring teacher’s performance; and (3) reflection on teacher’s ethics. These major changes are linked to the concepts of Foucault reveals that normalizing is emphasising to construct and target the teacher’s identities. The second concept is surveillance that is needed to maintain the regulations in every detail school, particularly on teacher’s performance. Lastly, reflection for ethical judgement and concern is essential in order to achieve moral conduct on teaching practice. Throughout this analysis, it shows that it is better if the government can fully identify the difficulty of teachers in order to establish the regulation. More importantly, giving more supports to provide sufficient facilities and programs that can be reached for all teachers is a recommended strategy. Keywords: Teacher’s role; Early Childhood Education; Indonesia